Design, computational modelling and experimental characterization of bistable hybrid soft actuators for a controllable-compliance joint of an exoskeleton rehabilitation robot - Dragone, Donatella; Randazzini, Luigi; Capace, Alessia; Nesci, Francesca; Cosentino, Carlo; Amato, Francesco; De Momi, Elena; Colao, Roberto; Masia, Lorenzo; Merola, Alessio (Actuators, 2022)
This paper presents the mechatronic design of a biorobotic joint with controllable compliance, for innovative applications of “assist-as-needed” robotic rehabilitation mediated by a wearable and soft exoskeleton. The soft actuation of robotic exoskeletons can provide some relevant advantages in terms of controllable compliance, adaptivity and intrinsic safety of the control performance of the robot during the interaction with the patient. Pneumatic Artificial Muscles (PAMs), which belong to the class of soft actuators, can be arranged in antagonistic configuration in order to exploit the variability of their mechanical compliance for the optimal adaptation of the robot performance during therapy. The coupling of an antagonistic configuration of PAMs with a regulation mechanism can achieve, under a customized control strategy, the optimal tuning of the mechanical compliance of the exoskeleton joint over full ranges of actuation pressure and joint rotation. This work presents a novel mechanism, for the optimal regulation of the compliance of the biorobotic joint, which is characterized by a soft and hybrid actuation exploiting the storage/release of the elastic energy by bistable Von Mises elastic trusses. The contribution from elastic Von Mises structure can improve both the mechanical response of the soft pneumatic bellows actuating the regulation mechanism and the intrinsic safety of the whole mechanism. A comprehensive set of design steps is presented here, including the optimization of the geometry of the pneumatic bellows, the fabrication process through 3D printing of the mechanism and some experimental tests devoted to the characterization of the hybrid soft actuation. The experimental tests replicated the main operating conditions of the regulation mechanism; the advantages arising from the bistable hybrid soft actuation were evaluated in terms of static and dynamic performance, e.g., pressure and force transition thresholds of the bistable mechanism, linearity and hysteresis of the actuator response.